2021
DOI: 10.1021/acs.jpca.0c08130
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigations of the Tropospheric Photooxidation Reactions of 1,1,1,3,3,3-Hexafluoro-2-Methyl-2-Propanol Initiated by OH Radicals and Cl Atoms

Abstract: The gas-phase kinetics for the reactions of OH radicals and Cl atoms with 1,1,1,3,3,3-hexafluoro-2-methyl-2-propanol (HF2M2P) were measured at temperatures between 268 and 363 K using the relative rate experimental technique. Methane and acetonitrile were used as reference compounds to measure the rate coefficients of the title reactions. For the reactions of HF2M2P with OH radicals and Cl atoms, the rate coefficients were measured to be ( 7.07 ± 1.21) × 10 −15 and (2.85 ± 0.54) × 10 −14 cm 3 molecule −1 s −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The M06-2X method is known to be a more reliable method to calculate the energetics, thermochemistry, and kinetics of atmospheric chemical reactions. Previous studies from many research groups and our group showed that the results obtained from the M06-2X method are comparable with the available experimental results.…”
Section: Resultssupporting
confidence: 82%
“…The M06-2X method is known to be a more reliable method to calculate the energetics, thermochemistry, and kinetics of atmospheric chemical reactions. Previous studies from many research groups and our group showed that the results obtained from the M06-2X method are comparable with the available experimental results.…”
Section: Resultssupporting
confidence: 82%
“…The kinetics of the corresponding reactions, representing the antioxidant property of each of the investigated drugs, which includes the reactants, transition states, complexes, and the products of the reaction with hydroperoxyl radicals, was investigated with the Minnesota hybrid meta functional M06-2X in conjugation with the 6-31+G­(d,p) basis set. M06-2X was employed because of its greater reliability in comparison with the B3LYP functional in kinetic calculations. In fact, the M06-2X method was specially developed for thermochemistry and kinetic study of chemical reactions and since then has been used extensively for studying H-abstraction reactions. The rate constant values obtained from the M06-2X method were comparable to the experimental results in a wide temperature range. Only the CCSD­(T) method with a reasonably good correlation consistent with the triple zeta basis set (like cc-pVTZ) can provide comparable/better results, but such a method could not be used due to the large size of the systems, and therefore, the M06-2X method was followed throughout in the present study.…”
Section: Computational Methodologymentioning
confidence: 89%